Top athletes` psychological characteristics and their potential for entrepreneurship - Steinbrink, K. M.; Berger, E. S. C.; Kuckertz, A. (International Entrepreneurship and Management Journal, 2020)
The role of personality traits as predictors of entrepreneurial intention and success has been widely researched. This article investigates the personality traits of top athletes practising low-risk- and high-risk-sports and, based on the person-job fit theory, compares them to the personality traits commonly associated with entrepreneurship. To achieve this aim, the big five personality traits and risk propensity of 43 non-athletes, 36 top athletes practising a low-risk-sport, and 31 top athletes practising a high-risk-sport are measured and analysed with an analysis of variance (ANOVA) and post-hoc tests. Furthermore, an explanatory approach is used to explain the similarities between the athletes` and the entrepreneurs` careers. The results show top athletes` personality traits match the detected directions for entrepreneurial intention and success, and the discussion examines whether entrepreneurship might be an appropriate second career choice for athletes. This study is based on data gathered from high-level competition athletes and thus makes it possible to draw inferences on the eligibility of athletes to become entrepreneurs based on their personality traits. The findings also signal the need for focused entrepreneurship education as well as an awareness among potential investors and future employers who could facilitate professional athletes becoming entrepreneurs and intrapreneurs.